Euconnus (Rhomboconnus) of Panama (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2017)
To date, the subgenus Rhomboconnus Franz of Euconnus Thomson was represented by two species known to occur in Venezuela and Ecuador. For the first time this subgenus is reported to occur in Panama, and eight new species are described: Euconnus plaumannioloides sp. n., E. timstruyvei sp. n., E. silvafortunensis sp. n., E. rhombopanamensis sp. n., E. rhombocartianus sp. n., E. meteti sp. n., E. rhombomiramaranus sp. n., and E. rhomboimitator sp. n. Some characters of the new species were found more variable than those previously included in the diagnosis of Rhomboconnus; they are discussed and the presence or absence of the pronotal antebasal groove or pits is excluded from the diagnosis, as variable within Rhomboconnus.